2012
DOI: 10.1042/bj20120200
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin and ouabain induce the efflux of cholesterol via liver X receptor signalling and the synthesis of ATP in cardiomyocytes

Abstract: Cardioactive glycosides exert positive inotropic effects on cardiomyocytes through the inhibition of Na(+)/K(+)-ATPase. We showed previously that in human hepatoma cells, digoxin and ouabain increase the rate of the mevalonate cascade and therefore have Na(+)/K(+)-ATPase-independent effects. In the present study we found that they increase the expression and activity of 3-hydroxy-3 methylglutaryl-CoA reductase and the synthesis of cholesterol in cardiomyocytes, their main target cells. Surprisingly this did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…The ATP reduction induced by ouabain was much less than that induced by cyanide and 2-deoxyglucosein, so the ATP loss observed in this experiment was likely caused by the increase of ATP consumption rather than the impairment of mitochondrial ATP synthesis. On the contrary, it has been shown that ouabain directly enhanced the rate of electron transport chain and the synthesis of ATP in cardiomyocytes via increasing the synthesis of ubiquinone [7]. These contradictory results might be due to differences in experimental conditions, animal species or tissue variations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The ATP reduction induced by ouabain was much less than that induced by cyanide and 2-deoxyglucosein, so the ATP loss observed in this experiment was likely caused by the increase of ATP consumption rather than the impairment of mitochondrial ATP synthesis. On the contrary, it has been shown that ouabain directly enhanced the rate of electron transport chain and the synthesis of ATP in cardiomyocytes via increasing the synthesis of ubiquinone [7]. These contradictory results might be due to differences in experimental conditions, animal species or tissue variations.…”
Section: Discussionmentioning
confidence: 98%
“…In previous animal and clinical studies, the arrhythmogenic effects of glycosides have been mainly attributed to NKA inhibition-induced Ca 2+ overload and associated abnormal RyR Ca 2+ release [2], [5], [7], [8], [44]. More recently, studies by Liu et al suggested that mitochondrial dysfunction, particularly ouabain-induced ROS production, might also contribute to the arrhythmogenic effect of glycosides [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin immunoprecipitation (ChIP) samples were prepared as previously reported using a ChIP‐tested anti‐c‐myc antibody (mouse clone 9E11; Abcam, Cambridge, UK). The putative c‐Myc binding site on ABCB5 promoter was validated with the Matinspector software (https://www.genomatix.de/matinspector.html).…”
Section: Methodsmentioning
confidence: 99%
“…ChIP samples were prepared as described by Campia et al 49,. using a ChIP-tested anti-LXRα antibody (61175, Active Motif, dilution 1/50).…”
Section: Methodsmentioning
confidence: 99%